Referenciação por estratégias anafóricas: a progressão referencial em textos de opinião - Carvalho, Luciene Euzébio de (2010)
This dissertation inserts in the research line Reading, Writing and Teaching of Portuguese Language and has as object of study the relevance of the anaphoras, marks that guarantee the progression of the felt reference and the construction of in the text. The difficulty of reading and understanding observed in classroom guided the accomplishment of this research.The objective of this work is to contribute for the studies of Portuguese Language with special prominence for the reading. The specific objectives are: 1 - To observe and to reflect on the strategies of referencing used by the reader to process the enrolled information in the opinion article, having for parameter the study of the anaphoric relations. 2 - To verify and to demonstrate the paper of the anaphoras to assure the progression semantics of the literal reference, as well as the production of decurrent direction of its use. To reach the objectives, we consider authors who deal with the referencing, as Mondada and Dubois (1995, 2003), Koch (2003, 2006), Koch and Elias (2006), among others. The referral strategies were discussed from the perspective of Apothéloz and Reichler-Béguelin (1995).Is the same lection by Koch and Elias (2006), Kleiman (2002), Pozo (2002), amongst others. About the study of genres and textual sequences the theoretical basement has for anchorage the studies of in Marcuschi (2005, 2006, 2008), of Bonini et. alli. (2005), of Adam (1992), and Charaudeau (2009). The results gotten in the analysis of the opinion article indicate that the anaphoric strategies guarante the progression of the reference in the text and by means of them if they provide directions that provide the reading comprehension, a time who they are linked to cognitive and linguistic processes.Therefore, the reading process is responsible for the deciphering both the textual strategies and cognitive that constitute the direction of the text